GENETIC ALGORITHM FOR HIGHER ENSURED LIFESPAN OF INTERNET OF THINGS IN 5G NETWORK. (March 2023) - Chandra, B Ravi; Kumar, Krishan; Roy, Ajay; Qamar, Shamimul; Rahman, Mohammed Inamur; Saif, Abdulelah G.F.
Abstract: The new 5th generation radio (NR) is being developed for the period of 5G to enable the elegant and inventive resources of the IoT. Battery life requires energy-efficient transfer protocols and efficient IOT coverage. The coverage challenge of IoTs with many nodes is broken down into numerous smaller problems in this paper, and problems are then solved in parallel using Hadoop. Finally, by deliberately spreading out the IoT's lifespan, parallel operation successfully resolves the coverage problem of the IoT through large nodes. The simulation analysis is done on performance measures for nodes' computing time, lifetime, and energy efficiency. The Genetic Algorithm (GA), Improved Genetic Algorithm Binary Ant Colony (IGA-BAC), and Improved Genetic Fast Non-Dominated Sorting Algorithm (IGA-FNS) are compared. The proposed (IGA-FNS) method achieves lower computation times of 5%, 12%, and 19%, a higher lifetime of 95.2%, 96.3%, and 97.6%, and fewer remaining nodes of 51%, 42%, and 46%, respectively.